GENOTYPE BY ENVIRONMENT AND PHENOTYPIC ADAPTABILITY STUDIES FOR YIELD AND FIBER VARIABLES IN UPLAND COTTON - S. Gul; N. U. Khan; R. Gul; M. Baloch; A. Latif; I.A. Khan (Journal of Animal and Plant Sciences, 2016)
Identification of adaptable and stable genotypes is an important aspect of applied plant breeding which can insure sustainable crop production. Adaptability studies in cotton is an essential part of breeding for adequate evaluation of genotypes accomplished through environments (years/locations). Present studies were conducted in a randomized complete block design with three replications during 2010 and 2011 to evaluate adaptability of eight upland cotton genotypes through genotype by environment interaction (GEI). Genotype (G), environment (E) and GEI share in total sum of squares were also studied. Significant (p≤0.01) differences were observed among genotypes, environments (years) and G × E interaction means for majority traits, which assured greater genetic variability among the genotypes due to their divergent genetic make-up, as well as environments. The contribution to total sum of squares regardless of trait revealed that environments (0.42 to 89.55%) and genotypes (5.02 to 46.21%) play principal role followed by genotype × environment (3.40 to 40.00%), while experimental error share was negligible (0.12 to 21.37%). Larger effects of environment in combination with genotypes persuade the plant growth and morphology. Based on two-year studies, genotype CIM-496 showed best performance for seed cotton and fiber yields and its contributing traits followed by cultivars CIM-554 and SLH-284. Seed cotton yield revealed significant positive correlation with majority traits. The above promising genotypes could be further explored for improvement in seed cotton and lint yields.
Keywords: Genotypes; environments; genotype-by-environment interaction; genotypic malleability; correlation; Gossypium hirsutum L